1953
DOI: 10.1210/endo-52-4-448
|View full text |Cite
|
Sign up to set email alerts
|

THE IN VIVO METABOLISM OF CORTISONE1

Abstract: T HE application of paper chromatography and infra-red spectrometry has permitted the isolation and identification of the major C-21 and C-19 metabolites excreted in urine, following the administration of adrenosterone hydro cortisone and 21-desoxycortisone . It has been shown that the C-21 steroids are reduced in the human body to the pregnane (5/3) and transformed to the corresponding C-19 etiocholane (5/3) derivatives. On the other hand, the A 4 -3 keto system in adrenosterone is converted predominantly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0

Year Published

1956
1956
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 0 publications
4
20
0
Order By: Relevance
“…This scheme is based on the work of a number of investigators (17,18,36) and has recently been reviewed by Bush (24). The position of allo-THF in this scheme is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scheme is based on the work of a number of investigators (17,18,36) and has recently been reviewed by Bush (24). The position of allo-THF in this scheme is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Although a considerable amount of work has been done in isolating and identifying such urinary metabolites of cortisol as THF8 and THE (17)(18)(19)(20)(21)(22) and their interconversions (23)(24)(25), much less has been done to relate the quantitative transformations of these urinary metabolites from cortisol under normal and pathological conditions. In 1953, deCourcy, Bush, Gray, and Lunnon (26) reported daily excretion values for two chromatographically separated urinary steroids corresponding in migration rates to THF and THE, in 10 1 This work was suported in part by a grant from the Atomic Energy Commission.…”
mentioning
confidence: 99%
“…Jayle, Desgrez, Serpicelli and Rozeg (11), Devis (12), Mills (13), and Appleby and Norymberski (14) found that the rise in urinary 17-OH-corticosteroids and 17-ketogenic steroids during pregnancy was of only moderate degree. Contradictory results have been obtained from studies of urinary 11-oxygenated 17-ketosteroids, the principal C19 metabolites of hydrocortisone (15). Dobriner, Lieberman, Rhoads and Taylor (16) and Davis and Plotz (17) reported that urinary 11-oxygenated 17-ketosteroids did not increase with advancing gestation, while Huis in't Veld (18) and Birke, Gemzell, Plantin and Robbe (19) claimed that these steroids were present in increased quantity in the third trimester.…”
mentioning
confidence: 99%
“…The interstitial cells obtained from 5 to 6 rats were further fractionated by centrifugation on continuous Percoll gradients as previously reported (Browning et al, 1981 (Bedin et aL, 1988a (Payne and Kelch, 1975 (Lykkesfeldt et al, 1985b;Ruokonen et t aL, 1986;Bedin et aL, 1988b (Burstein and Dorfman, 1963), it is tempting to speculate that the enzymatic activity present in microsomes prepared from whole testis homogenates reflects the Leydig cell STS. Another, argument in favour of such a similarity between Leydig cells and whole testicular microsomes in terms of STS activity is that hCG treatment modulates the enzyme expression in the latter preparation in a manner similar to that previously reported for Leydig cells (Bedin et aL, 1988a (Payne and Kelch, 1975).…”
Section: Tissue Preparationsmentioning
confidence: 92%